Budget Politics in Indonesia: A Case Study of the House of Representative's Optimization Fund - Muhammad Dimyati Sudja; Kumba Digdowiseiso; Banu Abdillah; Aditya Kusuma Rachman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study explores the nature of public budgeting through a study of the interaction between formal political institutions and informal practices in the Indonesian budget arena after the 2014 General Election. The study draws on a collection of theories related to the role of political institutions in budget making and engages in theoretical debates in a field study of the key roles of politicians and parties in the Indonesian political system since the advent of democracy. Based on data collected through literature studies, this study examines legislative behavior in the budget-making process. Based on the case study, that the relationship between the legislature and political parties and the behavior of the executive government is influenced not only by the constitutional power of the President in the budget, but also by electoral rules that encourage legislators to prioritize access to patronage resources over party affiliation. In other words, the budget-making process is driven by a combination of the executive's need to advance its budget agenda in a multiparty presidential setting, in the absence of party direction and discipline, and the legislator's need to secure patronage resources. These findings offer new insights not only into the budget process but also into the workings of the Indonesian legislature. First, the case studies show that the presence or absence of a governing coalition is not the main determining factor in providing stability in the budget decision-making process. Second, they point out that, in the absence of an effective coalition, the use of constitutional budget-making powers to retain support from the legislature comes at a very high political cost. Third, this study reveals a form of cartel-like behavior among individuals, not parties, which challenges the application of cartel party theory in the Indonesian context.